ALLAH SEBAGAI PARSONDUK: PEREMPUAN PEMIMPIN DALAM KONTEKS GEREJA KRISTEN PROTESTAN SIMALUNGUN DAN MASYARAKAT SIMALUNGUN - Jusni H Saragih; Irene Umbu Lolo; Minggus Minarto Pranoto (Sekolah Tinggi Theologia Abdiel, 2019)
This paper discusses a constructive theology by exploring the theme of Parsonduk in the context of Gereja Kristen Protestan Simalungun and its culture. The author uses feminist perspective to give a new meaning of Parsonduk. The original meaning of Parsonduk is a woman who feeds or spoonfeeds her family. The women in Simalungun‟s culture prepare the need of food for their families daily. Actually, this task is judged as the domestic work in the patriachal society. The task as Parsonduk is to serve the members of family such as husband and children. This paper recontructs theologically the meaning of Parsonduk by comparing the work fo God as the helper of Israel. The aim is to emphasize the important task of women at Simalungun‟s culture and to appreciate their role in the light of egaliterian perspective. Both men and women deserve to have the same opportunity to be leader in the church and society.